The role of osteopathic manipulative treatment in neurological disorders: A critical review with clinical advice - Mirjam Bonanno; Francesco Cerritelli; Rocco Salvatore Calabrò (Heliyon, 2025)
Background: Since more people age and live longer with chronic disease, it is important to develop complementary and adjunctive approaches to improve body homeostasis and ensure the highest possible level of well-being for people affected by neurological disorders, besides the known benefits related to neurorehabilitation. In this context, osteopathic manipulative treatment (OMT) should be considered a promising holistic treatment to manage better pain and symptoms related to the chronic stages of neurological diseases. Objective: The primary purpose of this review is to examine the existing literature to determine the role and effects of OMT in patients affected by neurological disorders, giving some clinical advice. Methods: This critical review followed the Preferred Reporting Items for Systematic and Meta-analyses extension for Scoping Review (PRISMA-ScR). To guarantee a comprehensive and up to date search of evidence, the following databases were consulted: PubMed, Google Scholar, OSTEOMED.DR, Scopus and Cochrane library. Results: After an accurate screening, we included 16 primary research articles about the use of OMT in patients affected by neurological disorders, such as Parkinson disease, multiple sclerosis, cerebral palsy, and spinal cord injury. Conclusion: This critical review supports the idea that OMT could be a useful complementary tool in neurorehabilitation. However, further research is needed to bridge the gap between research and clinical practice. Registration protocol: 10.17605/OSF.IO/HDSXC.